PELATIHAN USAHATANI BUDIDAYA SAYURAN DENGAN METODE HIDROPONIK PADA ANGGOTA KOPERASI SIMPAN PINJAM CREDIT UNION DAYA LESTARI UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA DI KECAMATAN TANJUNG REDEB - Galingging, Herwan; Haq, Arsyadani Sabilal (Universitas 17 Agustus 1945 Samarinda, 2024)
This community service activity aims to; 1). Providing science materials and mastery of hydroponic technology for KSP members. Credit Union Daya Lestari TP Kita Bersaudara in Tanjung Redeb District. 2). Providing agricultural science materials and investment criteria for the payback period (PP) of vegetable cultivation using the hydroponic method. 3). Developing the skills of KSP members. Credit Union Daya Lestari TP Kita Bersaudara in trying to grow vegetables through the application of a hydroponic system. In addition, through this community service activity, it is hoped that it can provide several benefits to the community, including; 1). Increase knowledge and mastery of hydroponic technology for vegetable cultivation to members of the TP Kita Bersaudara Daya Lestari Credit Union. 2). Increased knowledge of members of the TP Kita Bersaudara Daya Lestari Credit Union regarding the payback period investment criteria for the hudroponic vegetable farming project. 3). Increase the income of cooperative members through the application of hydroponic technology for vegetable cultivation. 4). The increase in the number of KSP members. Credit Union Daya Lestari TP Kita Bersaudara who farms hydroponic vegetables. 5). Hydroponic vegetable farming contributes to farmers' household income. This training and mentoring activity was carried out in Tanjung Redeb Village, Tanjung Redeb District. The results of a study on a cooperative member who farms vegetables by implementing hydroponic technology showed that there was an increase in income for farmer households/cooperative members because the income from vegetable farming contributed to family income of 38.83%.